Evaluation performance of OFDM system using the selected mapping technique for WIMAX technology - Khalifa, Mohamed Saleh (2015)
Orthogonal Frequency Division Multiplexing (OFDM) is a promising technique used in the wireless broadband communication systems these days. It is a form of multicarrier modulation technique with high spectral efficiency, robustness to channel fading, immunity to impulse interference, uniform average spectral density, capacity to handle very strong echoes and very less nonlinear distortion are the properties of the OFDM. One major disadvantage of OFDM is that the time domain OFDM signal which is the sum of several sinusoids leading to high peak to average power ratio (PAPR). This work, a technique is proposed in the literature for reducing the PAPR in OFDM systems selected mapping technique (SML) for reducing the PAPR in the simulation result shows the PAPR reduction of OFDM signals. The aim is to come up with an approach for a new modified selected mapping (SLM) technique. The modified technique has the inclusion of the idea of sub block partitioning of signals. The comparative analysis between the conventional SLM scheme and the modified SLM scheme shows that the modification gives better complementary cumulative distributive function (CCDF) of the PAPR of transmitted signal.